2018
DOI: 10.1177/1741143218792912
|View full text |Cite
|
Sign up to set email alerts
|

Relational trust and positional power between school principals and teachers in Chile: A study of primary schools

Abstract: The article analyses the trust relationship between principals and teachers in primary schools in the specific Chilean educational context. The analysis is based on the concept of school trust, emphasizing Bryk and Tschannen-Moran’s classic works. A mixed sequential quantitative–qualitative research methodology is used, including both a survey and a qualitative case study carried out in nine schools. The main results, include: principals and teachers take a different approach when forging trust they have in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 36 publications
0
20
1
9
Order By: Relevance
“…Trust facilitates the development of productive social relationships for school improvement and teacher collaboration, parent involvement, and student engagement in learning in the high-power distance school context (Li, Hallinger, & Walker, 2016). Trust between school principals and teachers could cooperate to make school successful and also makes the parents involved in the school activity (Cosner, 2009) and encourage the student to develop their learning outcomes (Crane, 2020;Weinstein, Raczynski, & Pena, 2020;. Creating a trust learning environment could promote the educational core values of benevolence, honesty, loyalty, and openness to both achieve school targets and school learning outcomes (Weinstein, Raczynski, & Pena, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust facilitates the development of productive social relationships for school improvement and teacher collaboration, parent involvement, and student engagement in learning in the high-power distance school context (Li, Hallinger, & Walker, 2016). Trust between school principals and teachers could cooperate to make school successful and also makes the parents involved in the school activity (Cosner, 2009) and encourage the student to develop their learning outcomes (Crane, 2020;Weinstein, Raczynski, & Pena, 2020;. Creating a trust learning environment could promote the educational core values of benevolence, honesty, loyalty, and openness to both achieve school targets and school learning outcomes (Weinstein, Raczynski, & Pena, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Schools are no stranger to challenging power relations (Weinstein, Raczynski & Pena, 2018). Hence, the power structure is an important construct to understand school settings and the relationship between parents, teachers, students, or school directors.…”
Section: Power In Schoolmentioning
confidence: 99%
“…Trust is a key element that keeps several components in schools together (Tschannen-Moran, 2014). Schools with weak trust relationships would not have cultivated an atmosphere of, or achieved improvement (Weinstein et al, 2018). Van Maela, Forsyth and Houtte (2014) found that the trust relationship is higher in the ethnically homogenous schools and lower in culturally diverse schools.…”
Section: Trust In Schoolmentioning
confidence: 99%
See 2 more Smart Citations